Synthesis and Spectro-Kinetic Study of the Complexes of Pd+2 Ion with 2-(5-Bromo-2- pyridylazo)5diethylaminophenol Reagent in Ethanol – Water Solutions - Ibrahim, Muayed khaleel (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The complexes of Pd+2 ion with 2-(5-bromo-2-pyridylazo)-5-dieÄ±hyl aminophenol (BPADAP) were studied kinetically and spectrophotometrically in aqueous ethanolic solutions. The reagent forms 1:1, 2:1 square planer and 1:1 bridged shape binuclear complexes with Pd+2 ion. All these complexes (violet colour) absorb light in the same region at 540, 575 and 618nm. The band at 618 nm seems to be specific for complexes of Pd+2ion with BPADAP.   The rate constants of the growth in 93% H2O + 7% ethanol of 1:1 and 2:1 complexes at 575 and 618 nm were followed the first order kinetics and are quite of the same values , 0.495 and 0.463 min- 1  respectively. The rate constants of the decay of 2:1 complex at 618 and 575 nm were followed the first order kinetics; their values are 0.075 and 0.065 min-1 respectively which are slower than the rate of the decay of 1:1 complex. Whereas, the rate constants of the growth and decay of 1:1 bridged binuclear complex also followed the first order kinetics but they are much slower than those of 1:1 and 2:1 complexes: the values of the growth are 025min-1at 575 nm , and 0.16 min-1 at 618 nm. And the values of the decay are 0.0476 min-1 at 575 nm and 0.008min-1 at 61 8 nm.   It was  found that BPADAP can identify and detect in ethanol at 575 and 618 nm less than one microgram up to more than seven micrograms of Pd+2 ion . The interference of UO2+2, Th+4, Pb+2 , Cd+2,Bi+3, Hg+2 and Zn+ 2 in the detection of Pd+2 ion at 575 nm ranges between (25.3 - 67)%. Whereas, the interference of these ions with the detection at 618 nm is only between (2.3 -3.9) %, so it is reasonable to suggest that BPADAP is a specific reagent for Pd+2 ion at 618 nm